1996
DOI: 10.1130/0091-7613(1996)024<0527:seotcc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of the Chicxulub crater

Abstract: Analyses of geomorphic, soil, and topographic data from the northern Yucatan Peninsula, Mexico, confirm that the buried Chicxulub impact crater has a distinct surface expression and that carbonate sedimentation throughout the Cenozoic has been influenced by the crater. Late Tertiary sedimentation was mostly restricted to the region within the buried crater, and a semicircular moat existed until at least Pliocene time. The topographic expression of the crater is a series of features concentric with the crater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Before the drilling of the ICDP Yaxcopoil-1 (Yax-1) borehole, several geophysical surveys were conducted in the area, such as seismic reflection (Bell et al 2004;Snyder and Hobbs 1999;Brittan et al 1999;Morgan and Warner 1999;Christeson et al 1999), aeromagnetism (Pilkington et al 2000;Ortíz-Alemán 1999), gravimetry (Sharpton et al 1992;Hildebrand et al 1991), and several other surveys (CamposEnriquez 1997; Pope et al 1996). With these data available, during a workshop sponsored by ICDP in the city of Mérida in 1998, a group of 14 scientists discussed drilling a deep scientific borehole within the crater limits (UrrutiaFucugauchi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Before the drilling of the ICDP Yaxcopoil-1 (Yax-1) borehole, several geophysical surveys were conducted in the area, such as seismic reflection (Bell et al 2004;Snyder and Hobbs 1999;Brittan et al 1999;Morgan and Warner 1999;Christeson et al 1999), aeromagnetism (Pilkington et al 2000;Ortíz-Alemán 1999), gravimetry (Sharpton et al 1992;Hildebrand et al 1991), and several other surveys (CamposEnriquez 1997; Pope et al 1996). With these data available, during a workshop sponsored by ICDP in the city of Mérida in 1998, a group of 14 scientists discussed drilling a deep scientific borehole within the crater limits (UrrutiaFucugauchi et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In UNAM-6 borehole the upper breccias are not present, indicating a major hiatus. Considering a diameter of the crater between 180 and 200 km (Hildebrand et al, 1991;Pope et al, 1996;Urrutia-Fucugauchi et al, 2004a) and the location of the boreholes from the center of the crater (UNAM-5, 110 km; UNAM-6, 152 km and UNAM-7, 127), we interpret the low apparent sedimentation rates as a consequence of a hiatus between the top of the impact breccias and the base of the Tertiary carbonates. Studies based on microfossils, stable isotopes and magnetostratigraphy from borehole Yaxcopoil-1 drilled within the crater reported a hiatus between the top of the impact breccias and the base of the Tertiary carbonate sequence (Keller et al, 2004;Rebolledo-Vieyra and UrrutiaFucugauchi, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…4). Urrutia-Fucugauchi et al (1996, 2004b reported results on the behavior of the magnetic susceptibility in boreholes UNAM-6 and UNAM-7 and Yaxcopoil-1; we extended the study on these boreholes and in addition included UNAM-5. Our aim has been to obtain high-resolution magnetic susceptibility logs to characterize the impact lithologies.…”
Section: Methodsmentioning
confidence: 99%
“…There is rapid drainage of seasonal rainfall into the karst limestone underground. Mayapán's location was probably determined in part by the density of water bearing cenotes in the area [1,2] as it is near a "ring of cenotes" around the brim of the Chicxulub crater [4], a zone that has a large number of archaeological sites [5]. …”
Section: The Site and Its Settingmentioning
confidence: 99%